2021
DOI: 10.1177/07419325211063491
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Meta-Analyses in Special Education: Exploring the Evidence Base for High-Leverage Practices

Abstract: It is crucial that special education teachers are equipped with the knowledge and skills necessary to improve outcomes for students with disabilities. Despite federal legislation and efforts of the field to identify and disseminate evidence-based practices for students with disabilities, it is uncertain whether all special education teachers provide instruction based on the best available research. To better prepare special education teachers, McLeskey et al. proposed 22 high-leverage practices (HLPs). We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…They further outlined the importance of providing students with opportunities to investigate real‐world problems and providing instruction that is student centered and bound by personal experiences that build on students' background knowledge, cultural values, and communication preferences. Identification of these evidence‐based practices confirms the relationship between CRP and HLP (Hunter et al, 2021; Klingner et al, 2014; Linan‐Thompson et al, 2018; Nelson et al, 2021; Orosco & Abdulrahim, 2017; Orosco & O'Connor, 2014). Finally, Aceves and Orosco posited that culturally responsive classrooms create assessments that “consider the students' linguistic and cultural identities” (p. 18).…”
Section: Theoretical Frameworkmentioning
confidence: 60%
See 3 more Smart Citations
“…They further outlined the importance of providing students with opportunities to investigate real‐world problems and providing instruction that is student centered and bound by personal experiences that build on students' background knowledge, cultural values, and communication preferences. Identification of these evidence‐based practices confirms the relationship between CRP and HLP (Hunter et al, 2021; Klingner et al, 2014; Linan‐Thompson et al, 2018; Nelson et al, 2021; Orosco & Abdulrahim, 2017; Orosco & O'Connor, 2014). Finally, Aceves and Orosco posited that culturally responsive classrooms create assessments that “consider the students' linguistic and cultural identities” (p. 18).…”
Section: Theoretical Frameworkmentioning
confidence: 60%
“…The integration of culturally responsive instruction is particularly important for ELs with LD as they may experience learning challenges in a new language and in adapting to mainstream culture at school. Orosco and O'Connor found that students benefit when teachers include explicit instruction, use targeted questioning, provide support in reading instruction, and incorporate opportunities for collaborative learning, which align with HLP in special education (Nelson et al, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, McLeskey et al (2017) identified 22 HLPs in special education that “occur with high frequency, can be mastered by novice teachers, preserves the integrity and complexity of teaching, and is based on research” (G. Nelson et al, 2021, p. 1).…”
Section: Preparation and Professional Development For Special Educato...mentioning
confidence: 99%